2D Based Puppet Character Introduction Game Using Construct 2 - Siska Dyah Pertiwi; Cindy Taurusta; Mohammad Suryawinata; Yulian Findawati (Procedia of Engineering and Life Science, 2021)
Indonesia has a very diverse culture. As in Java, many people still use Javanese language and have their own special art namely wayang. Many people now do not know about who the puppet characters, education has an important role to develop the potential and character of children. Fun learning media is needed by students. This research uses library study methods and interview to elementary school teachers. This game covers Javanese language subjects in grade 3-5, especially discussing material about puppet characters. Materials used under the 2013 Curriculum. This game has 3 level stages. In each game, players must collect 3 puppet after which the player will get the final score and also information about the puppets material adjusted to the level of Class. Also conducted 4 test with an average percentage of 98% and get a good response.